2010
DOI: 10.1681/asn.2009040412
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Graft Function and the Risk for Death with a Functioning Graft

Abstract: Delayed graft function (DGF) associates with an increased risk for graft failure, but its link with death with graft function (DWGF) is unknown. We used the US Renal Data System to assemble a cohort of all first, adult, deceased-donor kidney transplant recipients from January 1, 1998, through December 31, 2004. In total, 11,542 (23%) of 50,246 recipients required at least one dialysis session in the first week after transplantation. Compared with patients without DGF, patients with DGF were significantly more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
139
3
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(149 citation statements)
references
References 22 publications
1
139
3
6
Order By: Relevance
“…IR rates following transplantation are increasing (2), and kidney graft survival is worse in recipients with significant IR injury (3). Donor-reactive T cells and anti-HLA antibodies are established mediators of transplant injury and must be controlled by appropriate immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…IR rates following transplantation are increasing (2), and kidney graft survival is worse in recipients with significant IR injury (3). Donor-reactive T cells and anti-HLA antibodies are established mediators of transplant injury and must be controlled by appropriate immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 34 studies showed a 41% increase in long-term graft loss and a 38% relative increase in acute rejection in patients who developed DGF after renal transplantation (1). DDK transplant recipients with DGF were more likely to die with a functioning graft than were those without DGF (2). Data from United States scientific registries have shown an increase in the rate of DGF, from 14.7% during 1985-1992 to 23% for the 1998-2004 transplant cohorts (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…DDK transplant recipients with DGF were more likely to die with a functioning graft than were those without DGF (2). Data from United States scientific registries have shown an increase in the rate of DGF, from 14.7% during 1985-1992 to 23% for the 1998-2004 transplant cohorts (2,3). This increase has been contemporaneous with the use of expanded-criteria donor (ECD) and donation of kidneys after cardiac death.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The increased risk of rejection is seen with both cadaveric 3 and live donor 4 organs, and also, it is associated with increased recipient mortality. 5,6 Furthermore, long-term survival is worse in DGF kidney grafts, and there is an increasing recognition that ongoing inflammation drives interstitial fibrosis/tubular atrophy (formerly known as chronic allograft nephropathy) [7][8][9] and may limit average duration of transplant survival.…”
mentioning
confidence: 99%